Earth science - Tarbuck, Edward J.; Lutgens, Frederick K. (New York : Macmillan College Publishing, 1994)
Environment Management
Keywords: Earth sciences; Population; Natural resources; Weather; Mass wasting; Earthquakes; Mountain building; Earth history; Oceans; Human impact; Solar system; Astronomical observations